Xylogalacturonan-enriched pectin from the fruit pulp of Adansonia digitata: Structural characterization and antidepressant-like effect. (15th June 2021) - Patova, O.A.; Luаnda, A.; Paderin, N.M.; Popov, S.V.; Makangara, J.J.; Kuznetsov, S.P.; Kalmykova, E.N.
Graphical abstract: Highlights: Xylogalacturonan-enriched pectin is water-soluble pectin from the baobab fruit pulp. Starch is co-extracted with pectin at long extraction times and temperatures. Part of α-Gal p A residues are 3- O -substituted with terminal β-Xyl p residues. Xylogalacturonan possesses an antidepressant-like effect. Abstract: The low methyl-esterified and acetylated xylogalacturonan (DM 20 %, DA 2 %, Mw ∼ 58 kDa) was isolated by water extraction for 4 h × 2 at 50 °C (yield 23 %) from the pulp of baobab fruit ( Adansonia digitata L.). Subsequent tightening of the conditions for water extraction by mean increasing the temperature to 70 °C and time to 12 h led to the co-extraction of small amounts of starch components and RG I with xylogalacturonan. Structural analysis (DEAE-cellulose ion-exchange chromatography, HPSEC, monosaccharide analysis, NMR spectroscopy) revealed that about 12 mol. % of 1, 4-linked α-Gal p A residues were substituted by single β-Xyl p residues at the O -3 position. The xylogalacturonan was found to possess an antidepressant-like effect in mice. The study offers using the baobab fruit as a rich source of soluble dietary fiber – water-soluble pectin with beneficial physiological effect.